IMPLEMENTASI DEMOKRASI DAN MASALAH KORUPSI DI INDONESIA (TELAH KRITIS TERHADAP PERILAKU KORUPSI PADA MASA TRANSISI DEMOKRASI) - Mahdi, Haris El; Pratiwi, Ratih Nur (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2011)
Democratization is an ongoing process, and one that is becoming increasingly irreversible. But, in most development countries the democracy is growing very slowly, including in Indonesia. The democracy transition in the country of Indonesia has been begun since thirteen years ago. The main problem of democracy transition in Indonesia is corruption. Worriedly, the corruption in Indonesia is becoming widespread from central to local level. This article argues that the problem of corruption eradication in Indonesia is not handled seriously by the elites (the government)Key words: Democracy, Democracy Transition, Corruption.